Genome-wide association study using family-based cohorts identifies the WLS and CCDC170/ESR1 loci as associated with bone mineral density. (December 2016) - Mullin, Benjamin; Walsh, John; Zheng, Hou-Feng; Brown, Suzanne; Surdulescu, Gabriela; Curtis, Charles; Breen, Gerome; Dudbridge, Frank; Richards, J.; Spector, Tim; Wilson, Scott
Abstract Background Osteoporosis is a common and debilitating bone disease that is characterised by a low bone mineral density (BMD), a highly heritable trait. Genome-wide association studies (GWAS) have proven to be very successful in identifying common genetic variants associated with BMD adjusted for age, gender and weight, however a large portion of the genetic variance for this trait remains unexplained. There is evidence to suggest significant genetic correlation between body size traits and BMD. It has also recently been suggested that unintended bias can be introduced as a result of adjusting a phenotype for a correlated trait. We performed a GWAS meta-analysis in two populations (totaln  = 6, 696) using BMD data adjusted for only age and gender, in an attempt to identify genetic variants associated with BMD including those that may have potential pleiotropic effects on BMD and body size traits. Results We observed a single variant, rs2566752, associated with spine BMD at the genome-wide significance level in the meta-analysis (P = 3.36 × 10 −09 ). Logistic regression analysis also revealed an association between rs2566752 and fracture rate in one of our study cohorts (P = 0.017, n  = 5, 654). This is an intronic variant located in thewntless Wnt ligand secretion mediator (WLS ) gene (1p31.3), a known BMD locus which encodes an integral component of the Wnt ligand secretion pathway. Bioinformatics analyses of variants in moderate LD with rs2566752 produced strong evidence for a regulatory role for the variants rs72670452, rs17130567 and rs1430738. Expression quantitative trait locus (eQTL) analysis suggested that the variants rs12568456 and rs17130567 are associated with expression of theWLS gene in whole blood, cerebellum and temporal cortex brain tissue (P = 0.034–1.19 × 10 −23 ). Gene-wide association testing using the VErsatile Gene-based Association Study 2 (VEGAS2) software revealed associations between thecoiled-coil domain containing 170 (CCDC170 ) gene, located adjacent to theoestrogen receptor 1 (ESR1 ) gene, and BMD at the spine, femoral neck and total hip sites (P = 1.0 × 10 −06, 2.0 × 10 −06 and2.0 × 10 −06 respectively). Conclusions Genetic variation at theWLS andCCDC170/ESR1 loci were found to be significantly associated with BMD adjusted for only age and gender at the genome-wide level in this meta-analysis.